Monetary normalizations and consumer credit: Evidence from Fed liftoff and online lending - Christoph Bertsch; Isaiah Hull; Xin Zhang (Sveriges Riksbank, 2017)
On December 16th of 2015, the Fed initiated "liftoff", a critical step in the monetary normalization process. We use a unique panel dataset of 640,000 loan-hour observations to measure the impact of liftoff on interest rates, demand, and supply in the online primary market for uncollateralized consumer credit. We find that credit supply increased, reducing the spread by 16% and lowering the average interest rate by 16.9-22.6 basis points. Our findings are consistent with an investor-perceived reduction in default probabilities; and suggest that liftoff provided a strong, positive signal about the future solvency of borrowers.
Keywords: D14; E43; E52; G21; 330; monetary normalization; monetary policy signaling; consumer loans; credit risk